Role and regulators of N6-methyladenosine (m6A) RNA methylation in inflammatory subtypes of asthma: a comprehensive review - Gao, Ge; Hao, Yu Qiu; Wang, Chen; Gao, Peng (Frontiers in Pharmacology, 2024)
Asthma is a common chronic inflammatory disease of the lungs and airway, yet its inflammatory subtypes and potential pathogenesis have not been completely elucidated and require further study. With advances in epigenetic development, methylation has emerged as a new direction for identifying and decoding the occurrence and subtype manifestations of asthma. N 6 -methyladenosine (m 6 A), an RNA methylation modification occurring in the N 6 -position of adenosine, is a prevalent epigenetic modification observed in eukaryotes. It exerts significant control over mRNA metabolism by regulating alternative splicing, stability, export, and translation. The dynamic process of m 6 A methylation plays a crucial role in the pathogenesis of asthma and is tightly regulated by three types of regulators: writers, readers, and erasers. This article provides a comprehensive review of the association between m 6 A regulators and the pathogenesis of inflammatory subtypes of asthma, such as involvement of inflammatory cells and related inflammatory response. Furthermore, the findings presented herein provide new insights and a solid foundation for further research on m 6 A mRNA methylation as biomarkers for the diagnosis and development of personalized treatment for different subtypes of asthma, particularly neutrophilic asthma and eosinophilic asthma.